Role of titanium in hydrogen desorption in crystalline sodium alanate (2005)
ABSTRACT: The role of Ti in improving the thermodynamics of hydrogen desorption in crystalline sodium alanate sNaAlH4d has been investigated by using the density functional theory. The total energy calculations reveal that Ti prefers to occupy the Na site over that of the Al site when the atomic energies are used as the reference. However, the use of the cohesive energies of Al, Na, and Ti leads to the Al site being the least unfavorable one. Irrespective of whether Ti occupies the Na or the Al site, the energy necessary to remove a hydrogen atom from Ti substituted sodium alanate is significantly lowered from that of the pure alanate. The understanding gained here may help in designing hydrogen storage materials suitable for industrial applications.